2018
DOI: 10.1111/efp.12448
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of pathogenic and endophytic Colletotrichum isolates from Licania tomentosa in Brazil

Abstract: Licania tomentosa (Chrysobalanaceae), also known as “oiti,” is a forest tree mainly used for urban afforestation in Brazil. Although anthracnose caused by Colletotrichum gloeosporioides is the main disease that threatens this tree, the identification of the species was based on morphological characteristics only. Owing to the need to use the molecular approach to pinpoint the identity of this pathogen with precision, the aim of this study was to identify endophytic and pathogenic Colletotrichum isolates from L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For example, Prihastuti et al (2009) have reported that endophytic C. fructicola , Colletotrichum siamense and Colletotrichum asianum isolated from healthy coffee berries ( Coffea arabica ) were pathogenic to coffee berries. Similarly, Waculicz‐Andrade et al (2017) and Lisboa et al (2018) have reported that endophytic Colletotrichum spp. were pathogenic to their hosts, citrus trees and Licania tomentosa , respectively.…”
Section: Discussionmentioning
confidence: 81%
“…For example, Prihastuti et al (2009) have reported that endophytic C. fructicola , Colletotrichum siamense and Colletotrichum asianum isolated from healthy coffee berries ( Coffea arabica ) were pathogenic to coffee berries. Similarly, Waculicz‐Andrade et al (2017) and Lisboa et al (2018) have reported that endophytic Colletotrichum spp. were pathogenic to their hosts, citrus trees and Licania tomentosa , respectively.…”
Section: Discussionmentioning
confidence: 81%
“…othonianum, Annona muricata, Ann. squamosa, Coffea sp., Fragaria × ananassa (Farr & Rossman, 2019) and Licania tomentosa (Lisboa et al., 2018). Colletotrichum erythrinae and C. gloeosporioides are known to parasitize E. variegata (Farr & Rossman, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To isolate the fungus, leaf fragments were transferred to a Petri dish containing potato dextrose agar (PDA) and incubated at 25°C under 12‐hr photoperiod. For isolation, the single conidial cultures and the morphological characterization were carried out according to Lisboa, Silva, Pinho, Pereira, and Furtado (2018). The isolates (COAD 2976 and COAD 2978) were deposited at Collection Otávio de Almeida Drumond at the Universidade Federal de Viçosa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2018 ) Licania tomentosa Chrysobalanaceae Oitizeiro Lisboa et al. ( 2018 ) Limonium sinuatum Plumbaginaceae Wavyleaf sea lavender CDFA ( 2016 ) Weir et al. ( 2012 ), Fuentes‐Aragón et al.…”
Section: Appendix a – Colletotrichum Fructicola Host Plantsmentioning
confidence: 99%